Genetic Melting Pot in Blacklegged Ticks at the Northern Edge of their Expansion Front. (1st July 2020) - Talbot, Benoit; Leighton, Patrick A; Kulkarni, Manisha A
Abstract: Blacklegged ticks ( Ixodes scapularis ) are considered to be the main vector of Lyme disease in eastern North America. They may parasitize a wide range of bird and mammal hosts. Northward dispersal of blacklegged ticks has been attributed largely to movement of hosts to areas outside of the current range of the tick, in conjunction with climate change. To better understand the drivers of range expansion in the blacklegged tick, we need investigations of the genetic connectivity and differentiation of tick populations at a fine spatial scale using appropriate markers. In this study, we investigated genetic connectivity and differentiation in blacklegged ticks, in an area of putatively recent advance in Ontario and Quebec, Canada, using microsatellite markers. Our findings suggest patchy differentiation of alleles, no spatial pattern of genetic structure, and genetic subdivision within sites, which are consistent with the very limited evidence available near the leading edge of range expansion of blacklegged ticks into Canada. These findings are consistent with the prevailing hypothesis, drawn from a variety of fields of study, suggesting that migratory birds from a variety of regions may be bringing hitchhiking ticks northward into Canada.